Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/apha.13806
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome accumulation during early phase resistance training in humans

Abstract: Aim To describe ribosome biogenesis during resistance training, its relation to training volume and muscle growth. Methods A training group (n = 11) performed 12 sessions (3‐4 sessions per week) of unilateral knee extension with constant and variable volume (6 and 3‐9 sets per session respectively) allocated to either leg. Ribosome abundance and biogenesis markers were assessed from vastus lateralis biopsies obtained at baseline, 48 hours after sessions 1, 4, 5, 8, 9 and 12, and after eight days of de‐training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Increased total RNA was also suggestive of ribosomal biogenesis since the majority of total RNA (>85%) is ribosomal RNA (Figueiredo & McCarthy, 2019 ). Other shorter‐term studies regarding humans and rats have observed an increase in total RNA and ribosome biogenesis during multiple sessions of isometric muscle training (Hammarstrom et al, 2022 ; Kotani et al, 2019 ; Kotani et al, 2021 ). The total RNA data of the present study suggest that heightened transcriptional output and ribosomal content persist several months after resistance‐type training; and thereby provide an underlying rationale for the preservation of long‐term muscle mass.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Increased total RNA was also suggestive of ribosomal biogenesis since the majority of total RNA (>85%) is ribosomal RNA (Figueiredo & McCarthy, 2019 ). Other shorter‐term studies regarding humans and rats have observed an increase in total RNA and ribosome biogenesis during multiple sessions of isometric muscle training (Hammarstrom et al, 2022 ; Kotani et al, 2019 ; Kotani et al, 2021 ). The total RNA data of the present study suggest that heightened transcriptional output and ribosomal content persist several months after resistance‐type training; and thereby provide an underlying rationale for the preservation of long‐term muscle mass.…”
Section: Discussionmentioning
confidence: 94%
“…Loading‐induced hypertrophy with transcriptional upregulation has been observed concomitant with nuclei accretion in various studies regarding both humans and rodents (Abou Sawan et al, 2021 ; Dungan et al, 2019 ; Goh et al, 2019 ; Hammarstrom et al, 2022 ; Lee et al, 2018 ; Mesquita et al, 2021 ; Murach et al, 2020 ). Bruusgaard et al in 2010 pioneered work utilizing a model of synergist ablation to cause hypertrophy followed by denervation‐induced atrophy to demonstrate that load‐induced gains in myonuclei could be long‐lasting after the termination of such exposure (Bruusgaard et al, 2010 ).…”
Section: Introductionmentioning
confidence: 98%
“…3 In the current issue of Acta Physiologica, Hammarström, Øfsteng and colleagues from the Inland Norway University of Applied Sciences present very interesting new information about ribosome accumulation during the early phase of resistance training and how this impacts on muscle traininginduced hypertrophy. 4 They studied eleven men and women, 18-35 years of age, with a low previous history of resistance training. The subjects performed resistance training involving 12 sessions of resistance exercise (RE, 3-4 sessions per week) of unilateral knee extension with alternating legs.…”
Section: E D I T O R I a L The Accumulation Rate Of Ribosomes Predict...mentioning
confidence: 99%
“…Total RNA is considered to be a valid proxy marker of ribosomal density 3 . In the current issue of Acta Physiologica, Hammarström, Øfsteng and colleagues from the Inland Norway University of Applied Sciences present very interesting new information about ribosome accumulation during the early phase of resistance training and how this impacts on muscle training‐induced hypertrophy 4 . They studied eleven men and women, 18‐35 years of age, with a low previous history of resistance training.…”
mentioning
confidence: 99%
“…21 The latter has emerged as a central regulator of load-induced ribosome biogenesis as UBF protein levels were strongly predictive of increases in total RNA in response to exercise training. 17 Activation of UBF by phosphorylation leads to the recruitment of transcription factor IA (TIF-1A) and selectivity factor 1 (SL1), which together forms the preinitiation complex required for activating the transcriptional machinery of Pol I. 22 Also, phosphorylation of TIF-1A at Ser 649 and Ser 633 promotes interaction with Pol I to induce pre-rRNA synthesis, 23,24 and is shown to increase robustly following an acute bout of resistance exercise.…”
Section: Introductionmentioning
confidence: 99%